Evaluation of visual function within the central 10 degrees using IMOvifa™ 24plus (1-2) - Yuki Takagi; Ryo Asano; Kana Yamashita; Yukihiro Sakai; Sho Yokoyama; Kei Ichikawa; Kazuo Ichikawa (PLoS ONE, 2025)
Purpose The IMOvifa™ perimeter with a 24plus (1-2) testing mode has additional measurement points within the central 10 degrees, which may help evaluate the visual field within this area. Here, we comparatively evaluated the IMOvifa™ 24plus (1-2) and HFA 10-2 for the first time. Methods We included 30 patients (48 eyes) who underwent HFA 24-2 Swedish Interactive Threshold Algorithm Standard and IMOvifa™ 24plus (1-2) Ambient Interactive Zippy Estimated tests on the same day and HFA 10-2 within six months. We used Spearman’s rank correlation coefficient to analyze the mean deviation (MD) and pattern standard deviation (PSD) between HFA 10-2 and IMOvifa™. The central 10-degree visual field was divided into four sectors, and concordance of visual field defects between IMOvifa™ 24plus (1-2) and HFA 10-2 was evaluated using kappa analysis. Additionally, all sectors showing a sensitivity of 0 dB on the HFA 24-2 were assessed for the presence and agreement of residual visual field in HFA 10-2 and IMOvifa™ 24plus (1-2). Results The MD (0.843/0.804) and PSD (0.852/0.763) of IMOvifa™ 24plus (1-2) and HFA 24-2 correlated strongly with those of HFA 10-2. Regarding the ability to detect visual field defects within the central 10 degrees, agreement with HFA 10-2 was κ = 0.715 (0.611,0.819) and 0.754 (0.654,0.854) for IMOvifa™ 24plus (1-2) and HFA 24-2, respectively. In the evaluation of residual visual field, IMOvifa™ 24plus (1-2) detected residual visual function in 100% of cases where HFA 10-2 indicated residual function. Conclusion The IMOvifa™ 24plus (1-2) may have a higher ability to detect defects in certain areas of the visual field, compared with HFA 24-2, and may also detect residual visual function. However, the IMOvifa™ 24plus (1-2) is difficult to substitute for the 10-2 test, as the 10-2 test is necessary for evaluating visual field defects within the central 10 degrees.